Language learning as a model of content learning in a collaborative university class - Ney, James W. (Lenguas Modernas, 2017)
Principles derived from the manner in which students master subject matter in a collaborative setting match rather closely principles used to describe how language is learned. These language learning principles inclucle the fact (1) that no one learns a language without interaction with other humans, the fact (2) that negative affect restricts language learning and positive affect facilitates language learning, the fact (3) that human beings learn language from a mal-formed corpus of the object to be learned and the fact (4) that students learn language only from comprehensible input. These four principles, derived from studies in language acquisition or learning, provide an explanation for the effectiveness of collaborative learning.